Nomenclatural novelties in Miconieae (Melastomataceae): new synonym and typifications - Valente, Beatriz Do Nascimento; Baumgratz, José Fernando A.; Maia, Vitor Hugo (Phytotaxa, 2020)
(Nomenclatural novelties in Miconieae (Melastomataceae): new synonym and typifications). This contribution provides diagnostic morphological characters, geographic distribution data, synonymizations and typifications for three species of Miconieae. We clarify the taxonomic status of Clidemia raddiana as a new synonym for Miconia capilliflora and designate its lectotype. For Miconia capillaris and Miconia leptopus, we provide nomenclatural adjustments, due to the similarity of the epithets and morphological characteristics. We also designate a lectotype and a neotype, respectively, for these two species.